2008
DOI: 10.2478/s11600-008-0016-z
|View full text |Cite
|
Sign up to set email alerts
|

Spatially-averaged oscillatory flow over a rough bed

Abstract: A rigorous framework involving flow decomposition and averaging is presented, within which the mechanics of rough-(e.g., rippled-) bed oscillatory flows can be better interpreted and understood. Spatiallyaveraged equations for conservation of fluid mass and momentum are developed for analyses of rapidly-changing bed conditions, e.g., for growing ripples. Where repeated observations of the changing bed conditions are available, the ensemble and spatially-averaged versions of these equations can be used for more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…In vertical to transverse profiles comparison, Papanicolaou and Hilldale [29] suggested that D 2 and λ 2 should be larger than D 3 and λ 3 , which is also agreed by our findings on all flows over hydraulically smooth, rough and water-worked beds. As shown in Table 2, all turbulence intensities D 1 , D 2 , D 3 , λ 1 , λ 2 and λ 3 in Figures 4-6 compare reasonably well with literature findings. Detailed comparison reveals that λ 1 is slightly higher than most proposed values.…”
Section: Turbulence Characteristicssupporting
confidence: 88%
See 1 more Smart Citation
“…In vertical to transverse profiles comparison, Papanicolaou and Hilldale [29] suggested that D 2 and λ 2 should be larger than D 3 and λ 3 , which is also agreed by our findings on all flows over hydraulically smooth, rough and water-worked beds. As shown in Table 2, all turbulence intensities D 1 , D 2 , D 3 , λ 1 , λ 2 and λ 3 in Figures 4-6 compare reasonably well with literature findings. Detailed comparison reveals that λ 1 is slightly higher than most proposed values.…”
Section: Turbulence Characteristicssupporting
confidence: 88%
“…This concept can create a non-moving deposited surface topography suitable to represent the natural open channel rough bed, which is usually produced in similar water-worked manner. As suggested by Coleman et al [3] after studying different forms of rough bed, the bed-form and its roughness can effectively alter the time-averaged spatial velocity and turbulence characteristics, particularly at inner flow region; thus, the water-worked bedform should impact the flow characteristics especially at near-bed flow.…”
Section: Introductionmentioning
confidence: 99%
“…The time varying spatially averaged shear stress contributions are examined following the stress partitioning scheme presented in Coleman et al . [] and Rodriguez‐Abudo and Foster []: τxz(z,truet)= μtrueuzρtrueutruewρfalse(ufalse)bfalse(wfalse)bρtrueuw˜, where u is the horizontal velocity ( x ‐coordinate), w is the vertical velocity ( z ‐coordinate), t represents the wave phase, over tilde ( true) denotes phase average, prime ( ) represents departure from the phase average ( ui=trueui+ui), angle brackets ( ) denote spatial average, and the subscript b represents departure from the spatial average ( trueui=trueui+false(ufalse)b). Expression (4) partitions the shear stress into a viscous component (first term), a convective momentum transfer term induced by the large scale hydrodynamics presented by waves and currents (and any other physics coherent with trueui, second term), a bed form‐induced momentum transfer term that arises due to the presence of an uneven boundary (third term), and the Reynolds (turbulent) stress (fourth term).…”
Section: Resultsmentioning
confidence: 99%
“…Similar to Coleman et al . [] τLWTρtrueu(z,truet)truew(z,truet), where u and w are approximated with LWT: trueu(z,truet)πHTcoshkzsinhkhcos(ωtruet) truew(z,truet)πHTsinhkzsinhkhsin(ωtruet). …”
Section: Resultsmentioning
confidence: 99%
“…It appears however that in terms of the magnitude,τ is generally lower than the shear stresses presented in figure 19, as was also the case for the other experiments, which are not presented here for brevity. The fact thatτ close to the bed is consistently lower than the bed shear stress estimates in figure 19 could be due to the presence of significant form-induced stresses which are not captured in (6.3), but require estimation of the the spatial-and time-averaged Reynolds equations (Coleman, Nikora & Schlicke 2008).…”
Section: Momentum Integralmentioning
confidence: 89%